Grammars of space explorations in cognitive diversity - Levinson, Stephen C. 1947-; Wilkins, David (Language, culture, and cognition, 2006)
Spatial language - that is, the way languages structure the spatial domain – is an important area of research, offering insights into one of the most central areas of human cognition. In this collection, a team of leading scholars review the spatial domain across a wide variety of languages. Contrary to existing assumptions, they show that there is great variation in the way space is conceptually structured across languages, thus substantiating the controversial question of how far the foundations of human cognition are innate. Grammars of Space is a supplement to the psychological information provided in its companion volume, Space in Language and Cognition. It represents a new kind of work in linguistics, 'Semantic Typology', which asks what are the semantic parameters used to structure particular semantic fields. Comprehensive and informative, it will be essential reading for those working on comparative linguistics, spatial cognition, and the interface between them